Quality Parameters of Mechanically Extracted Edible Macauba Oils (Acrocomia aculeata) for Potential Food and Alternative Industrial Feedstock Application. Issue 5 (19th March 2019) - Prates‐Valério, Pedro; Celayeta, Jesus M. F.; Cren, Erika C.
Abstract : There is a need for knowledge on new sources of vegetable oils. Acrocomia aculeata is regarded as a promising alternative source to meet food and industrial demands. With a similar productive potential to Elaeis guineensis, this crop is among the highest oil‐yielding plants in the world. The present study characterizes the A. aculeata oil comprehensively to aid the setting up of standards encompassing the quality, composition, and identity. Samples are obtained under five different pressing conditions and screened regarding quality parameters. The coldly pressed sample, which shows the highest tocols content (85.5 mg kg −1 ), the higher oil stability index (6.4 h), and an acid value of 1.6 mg KOH g −1 is characterized in terms of chemical, physical, and identity characteristics, i.e., peroxide value, insoluble impurities, mineral contents, fatty acids essential composition, iodine value, saponification value, kinematic viscosity, relative density, unsaponifiable matter, and total carotenoids. Results are compared with the literature sources to assess A. aculeata as an alternative feedstock. The study contributes to evidence that products derived from A. aculeata may have good consumer acceptance, nutraceutical value, and natural appeal. It is suggested that the compliance to legal standards must be pursued to guarantee the sustainability of the productive crop chain. Practical Applications : This paper contributes an assessment of the quality parameters of Acrocomia aculeata oils as Functional Food and alternative industrial feedstock. A comprehensive characterization of the oil studied will help food scientists, industry and food processing research to set up standards concerning composition, identity and health‐related topics regarding one of the highest oil‐yielding plants in the world. A comprehensive characterization of edible vegetable oils mechanically extracted from the mesocarp of fresh Acrocomia aculeata fruit is carried out to consider the assessment of different temperature conditions and subsequent pressings. Quality, composition, and identity characteristics of the crude oil are obtained to set up standards also on health‐related topics. Abstract : A comprehensive characterization of edible vegetable oils mechanically extracted from the mesocarp of fresh Acrocomia aculeata fruit is carried out to consider the assessment of different temperature conditions and subsequent pressings. Quality, composition, and identity characteristics of the crude oil are obtained to set up standards also on health‐related topics.